Answer:
Vf₂ = 2 Vf₁
It shows that final speed of Joe is twice the final speed of Jim.
Explanation:
First, we analyze the final speed of Jim by using first equation of motion:
Vf₁ = Vi + at
where,
Vf₁ = final speed of Jim
Vi = initial speed of Jim = 0 m/s
a = acceleration of Jim
t = time of acceleration for Jim
Therefore,
Vf₁ = at ---------------- equation (1)
Now, we see the final speed of Joe. For Joe the parameters will become:
Vf = Vf₂
Vi = 0 m/s
a = a
t = 2t
Therefore,
Vf₂ = 2at
using equation (1):
Vf₂ = 2 Vf₁
It shows that final speed of Joe is twice the final speed of Jim.